LTE-Advanced and IEEE 802.11ac. Issue 4 (3rd August 2015) - Yang, Samuel C.; Winter, Peter
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Mobile data traffic globally is increasing rapidly in both enterprise and consumer segments. The purpose of this paper is to identify a new network architecture and opportunity that support ubiquitous mobile work for higher-education institutions. Design/methodology/approach – It reviews existing literature and enabling technologies and proposes integrating both wide-area Long Term Evolution-Advanced (LTE-Advanced) and local-area IEEE 802.11ac networks for seamless, gigabit-speed services. A decision framework for moving toward such architecture and a cost/benefit analysis are also presented. Findings – Integrating both LTE-Advanced and IEEE 802.11ac networks for seamless connectivity is technically and organizationally feasible, provided that a higher-education institution has faculty and staff that require locational and interactional mobility. The cost/benefit analysis also shows that moving to the new architecture has potential benefits that can accrue to the higher-education institution. Research limitations/implications – With the coming availability of these wide-area and local-area gigabit networks, a new architecture that can ubiquitously supports mobile workers may be advantageous to universities and colleges. Originality/value – To the best of the authors' knowledge, this paper is one of the first that proposes such integrated architecture in the context of higher-education institutions. In addition to the examination of technological issues and proposed architecture, the decision framework, and cost/benefit analysis should be valuable for institutions contemplating the move toward the new architecture and for guiding further research in this area.